2005
DOI: 10.1097/01.bot.0000164338.79013.10
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Forearm Rotation After Tension-Band-Wiring Fixation of Olecranon Fractures

Abstract: The tension-band-wiring technique is a well-accepted method of internal fixation of olecranon fractures. In addition, it is suggested that transcortical placement of the k-wires results in lower rates wire migration. We encountered two clinical cases in which transcortical placement of the k-wires led to impairment of forearm rotation. An anatomic study was conducted to study the effect of transcortical wire placement to avoid similar future complications. Using specimens from 10 embalmed cadavers, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 12 publications
1
37
0
1
Order By: Relevance
“…In this study, it was hypothesized that these measurements of the proximal ulna were important to deal with the intra-articular appearance of K-wires during olecranon fixation with TBW. High correlation was found between the UL, POH and TW, and these results were interpreted as ''the individuals with shorter ulnae are more likely for the intraarticular appearance of K-wires'' [2,6,8].…”
Section: Posterior Olecranon Height and Trochlear Notch Widthsmentioning
confidence: 87%
“…In this study, it was hypothesized that these measurements of the proximal ulna were important to deal with the intra-articular appearance of K-wires during olecranon fixation with TBW. High correlation was found between the UL, POH and TW, and these results were interpreted as ''the individuals with shorter ulnae are more likely for the intraarticular appearance of K-wires'' [2,6,8].…”
Section: Posterior Olecranon Height and Trochlear Notch Widthsmentioning
confidence: 87%
“…Over the years, minor changes have been applied to optimize the technique of TBW, and the intra-and postoperative complications appear to be low in both frequency and severity. In contrast to the prevailing opinion, several case reports highlight major risks, such as damage to the median and anterior interosseous nerves, vascular lesions in the ulnar artery, Volkmann's contracture, radio-ulnar synostosis, heterotopic ossification and restriction in mobility [13,14,17,22,[31][32][33]. Most of these complications occur when the K-wires surmount the far cortex of the ulna.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the rotational position plays an important role in TBW. The forearm should be maximally supinated at 30°ulnar angulation when K-wires are inserted to prevent impingement of the radius and of soft tissues, such as the biceps tendon or the supinator muscle [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,24 Although the problem may be more frequent than actually reported, we were able to find only two reports of hardware impingement in the region of the proximal radius following fixation of an olecranon fracture. 3,18 In the first report, 3 the authors described two clinical cases in which bicortical placement of the Kirschner wires led to impaired forearm rotation with normal flexion and extension of the elbow. In the first case, the tip of the most radial Kirschner wire had penetrated the radial neck and the forearm was fixed in pronation.…”
Section: Discussionmentioning
confidence: 99%